Changes in Vitellogenin, Abdominal Lipid Content, and Hypopharyngeal Gland Development in Honey Bees Fed Diets with Different Protein Sources - Gunesdogdu, Mustafa; Sarioglu-Bozkurt, Aybike; Sekeroglu, Ahmet; Abaci, Samet Hasan (Mdpi, 2024)
Honey bees play an important role in the pollination of flowering plants. When honey bee colonies are deficient in pollen, one of their main nutrients, protein supplements are required. In this study, the effects of diets with six different protein sources on the physiological characteristics of worker bees (vitellogenin (Vg), abdominal lipid content (ALC), hypopharyngeal gland (HPG)) and consumption were investigated. The protein sources of the diets (diet I, & mldr;, diet VI) included pollen, spirulina dust (Arthrospira platensis Gomont), fresh egg yolk, lyophilized lactose-free skimmed milk powder, active fresh yeast, and ApiProtein. It was identified that consumption by worker bees was highest in the diet group supplemented with spirulina (diet II). Although there was no statistical difference regarding the Vg content in the hemolymph, numerically, the highest content was found in diet group IV (lyophilized lactose-free skimmed milk powder) (4.73 +/- 0.03 ng/mL). ALC and HPG were highest in the group fed diet II. These results suggest that offering honey bees diets with certain protein sources can support their physiological traits.
Keywords: Apis mellifera; physiology; diet; feeding